CO2 and CO emission rates from three forest fire controlled experiments in Western Amazonia - Carvalho, J. A. [UNESP]; Amaral, S. S. [UNESP]; Costa, M. A.M. [UNESP]; Soares Neto, T. G.; Veras, C. A.G.; Costa, F. S.; van Leeuwen, T. T.; Krieger Filho, G. C.; Tourigny, E.; Forti, M. C.; Fostier, A. H.; Siqueira, M. B.; et al. (My University, 2016)
Forests represent an important role in the control of atmospheric emissions through carbon capture. However, in forest fires, the carbon stored during photosynthesis is released into the atmosphere. The carbon quantification, in forest burning, is important for the development of measures for its control. The aim of this study was to quantify CO2 and CO emissions of forest fires in Western Amazonia. In this paper, results are described of forest fire experiments conducted in Cruzeiro do Sul and Rio Branco, state of Acre, and Candeias do Jamari, state of Rondônia, Brazil. These cities are located in the Western portion of the Brazilian Amazon region. The biomass content per hectare, in the virgin forest, was measured by indirect methods using formulas with parameters of forest inventories in the central hectare of the test site. The combustion completeness was estimated by randomly selecting 10% of the total logs and twelve 2 × 2 m2 areas along three transects and examining their consumption rates by the fire. The logs were used to determine the combustion completeness of the larger materials (characteristic diameters larger than 10 cm) and the 2 × 2 m2 areas to determine the combustion completeness of small-size materials (those with characteristic diameters lower than 10 cm) and the. The overall biomass consumption by fire was estimated to be 40.0%, 41.2% and 26.2%, in Cruzeiro do Sul, Rio Branco and Candeias do Jamari, respectively. Considering that the combustion gases of carbon in open fires contain approximately 90.0% of CO2 and 10.0% of CO in volumetric basis, the average emission rates of these gases by the burning process, in the three sites, were estimated as 191 ± 46.7 t ha-1 and 13.5 ± 3.3 t ha-1, respectively.
Keywords: Amazonia forest fires; Biomass consumption; CO emission; CO2 emission